LEADERSHIP 4.0 IN DIGITAL TRANSFORMATION OF THE MANUFACTURING SECTOR: A COMPARATIVE MULTI-CASE STUDY OF PT UNILEVER INDONESIA TBK AND PT INDOFOOD CBP - Nanlohy, Donasius Sagita (JURNAL ILMIAH EDUNOMIKA, 2025)
Digital transformation in the manufacturing sector requires a new form of leadership capable of integrating technology, people, and organizational processes in adaptive and synergistic ways. This study aims to analyze the patterns of Leadership 4.0 applied within the digital transformation processes of two major FMCG manufacturing companies in Indonesia, PT Unilever Indonesia Tbk and PT Indofood CBP. The research employs a qualitative approach using a comparative multi-case study design based on publicly available documentary sources, including annual reports, sustainability reports, official corporate publications, and credible business media articles. Data were collected through systematic document analysis and examined using content analysis, pattern matching, and cross-case synthesis to identify convergent and divergent characteristics of digital leadership practices across both cases. The findings show that Unilever adopts a Leadership 4.0 approach characterized by innovation-driven initiatives, sustainability integration, and structured digital capability development for employees. In contrast, Indofood applies a more efficiency-oriented leadership approach, focusing on operational stability, supply chain digitalization, and gradual implementation of digital technologies to enhance productivity. The comparative analysis reveals that differences in organizational culture, digital vision, and technology maturity significantly influence the forms and depth of Leadership 4.0 implementation within each company. This study contributes to the growing body of literature on digital leadership in the Indonesian manufacturing sector while providing practical insights for FMCG organizations navigating the complexities of digital transformation. Keywords : digital leadership, industry 4.0, leadership 4.0, manufacturing, digital transformation